The impact of entrepreneurial orientation on business performance: Mediating role of socio-emotional wealth in family businesses in West Sumatra, Indonesia - Primadona,; Emrizal, (International Journal of Management and Sustainability, 2025)
The social emotional wealth (SEW) of family members in managing the family business must be strengthened through innovation and creative thinking, which are part of Entrepreneurial Orientation (EO). Although much of the existing literature focuses on measuring research performance by prioritizing economic aspects, it often overlooks how SEW influences the management process in family businesses. This study examines whether EO, through SEW, affects performance in family companies in West Sumatra, Indonesia. It employs explanatory research with a survey method, utilizing a quantitative approach. Data were collected from 100 family businesses, and analysis was conducted using Structural Equation Modeling - Partial Least Square (SEM-PLS). The study hypothesizes that EO has a significant effect on business performance (BP) through SEW in family companies in West Sumatra, Indonesia. Limitations include the sample size, and future research could incorporate both qualitative and quantitative methods to explore SEW more deeply. The findings can contribute to the development of research on ethnic family businesses.